Metagenetic and Volatilomic Approaches to Elucidate the Effect of Lactiplantibacillus plantarum Starter Cultures on Sicilian Table Olives - Vaccalluzzo, Amanda; Celano, Giuseppe; Pino, Alessandra; Calabrese, Francesco Maria; Foti, Paola; Caggia, Cinzia; Randazzo, Cinzia (Frontiers in Microbiology, 2022)
The present study aimed to evaluate the effect of selected Lactiplantibacillus plantarum strains on both microbiota composition and volatile organic compound profile of Sicilian table olives. Two starter cultures were set up for pilot-plan scale fermentations at 5% (O1, O2). Un-inoculated table olives at 5 and 8% (C5 and C8) of salt were used as control. The fermentation process was monitored till 80 days through a dual approach which included both classical microbiological and amplicon-based metagenetics and volatilomics analyses. Compared to control samples (C5 and C8), experimental samples, inoculated with starter cultures (O1 and O2), exhibited a faster acidification with a more pronounced drop in pH. Metagenetics data revealed the dominance of the Lactobacillus genus in both experimental samples, through the whole fermentation period, and a concomitant reduction of Enterobacter sp occurrence. In particular, the dominance of L. plantarum species in inoculated samples was clearly highlighted together with the ability of inoculated strains to adhere to the drupe surface and to inhibit the spoilage bacteria. Furthermore, in experimental samples, volatilomics analysis revealed the presence of volatile organic compounds responsible of pleasant flavours whereas none compounds involved in off-odours metabolisms was detected.